A Comprehensive Understanding of Shukrala Karma in Male Infertility (AYUSHDHARA, 2021)
Male reproductive health depends upon the normal structures and functions of Shukrava srotas. Shukra is composed of both sperm and semen and considered one of the important factors for fertilization. It is stated as Phalavat shukra. Preceptors of Ayurveda have described eight types of Shukra dosha and their treatments. Low sperm count, decrease sperm motility, abnormal sperm morphology, ejaculatory problems, sexual dysfunctions, environmental exposures (radiation, pollution, and stress etc), lifestyle habits (smoking, alcohol, recreational drugs etc), varicocele, hormonal imbalances, DNA damage, and reactive oxygen species (ROS) etc are causative factors for Male infertility. Thousands of years back, ancient system of medicine has mentioned the word Purusha vandya (male infertility) and different pharmacological activities, medicinal formulas, therapies to treat sperm disorders, semen impairments, and sexual dysfunctions.Vajeekarana is one of the special branches of Astanga Ayurveda which maintains the fertility and management of male infertility. Shukrala, Shukra janana, Shukra shodhana, Shukra rechaka, Shukra pravataka and Shukra sthambhaka etc., are the pharmacological activities mentioned to treat Shukradoshas. Shukrala karma mainly composed of Shukra vrudhikara and Shukra srutikara means which enhances the Shukra (semen and sperm) quantitatively and qualitatively and facilitates its ejaculation. Therefore, an attempt has been made to establish the concept of Shukrala karma and its therapeutic applicability in the management of male infertility.